EFL Teachers’ Strategies in Implementing the 21st Century Skills Applied in 2013 Curriculum - Danul Aristiawan; Herman Herman (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
Curriculum is a guide that has a very crucial role in the learning process. As a guide that determines success in achievement in learning, it is necessary to make improvements in the preparation of the curriculum, therefore curriculum 13 is designed for learning in the 21st century. The aim of this research is to investigate the strategies of EFL teachers in applying the 21st century skills embedded in the 2013 curriculum. This research uses a qualitative research approach. Research data were obtained through in-depth interviews, document analysis, and observation. The data analysis in this research used descriptive qualitative. The findings of this study indicate that: 1) Four English teachers at SMAN 1 Pringgarata usedasking questions, group discussions, debates, role play, inquiry-based learning, project-based learning, and social media to teach, students acquire using these strategies learning skills, literacy skills, and life skills such as critical thinking, creativity, collaboration, communication, information literacy, media literacy, technology literacy, flexibility, social, and leadership skills in which these skills are embedded in 2013 curriculum 2) The problems faced by teachers were different characters of students, lack of student motivation, mastery of teaching strategies was low, crowded class, limited teaching time allotment, and lack of learning resources. 3) In overcoming this problem, the teacher offers several solutions to become an independent teacher in search of additional material, approaching students who have low motivation in class, have manuals to make the management class better, and use games in teaching to make learning fun.